Elimination of Undesirable Water Layers in Solid-Contact Polymeric Ion-Selective Electrodes - Veder, Jean-Pierre; De Marco, Roland; Clarke, Graeme; Chester, Ryan; Nelson, A.; Prince, K.; Pretsch, E.; Bakker, Eric (American Chemical Society, 2008)
This study aimed to develop a novel approach for the production of analytically robust and miniaturized polymeric ion sensors that are vitally important in modern analytical chemistry (e.g., clinical chemistry using single blood droplets, modern biosensors measuring clouds of ions released from nanoparticle-tagged biomolecules, laboratory-on-a-chip applications, etc.). This research has shown that the use of a water-repellent poly(methyl methacrylate)/poly(decyl methacrylate) (PMMA/PDMA) copolymer as the ion-sensing membrane, along with a hydrophobic poly(3-octylthiophene 2,5-diyl) (POT) solid contact as the ion-to-electron transducer, is an excellent strategy for avoiding the detrimental water layer formed at the buried interface of solid-contact ion-selective electrodes (ISEs). Accordingly, it has been necessary to implement a rigorous surface analysis scheme employing electrochemical impedance spectroscopy (EIS), in situ neutron reflectometry/EIS (NR/EIS), secondary ion mass spectrometry (SIMS), and small-angle neutron scattering (SANS) to probe structurally the solid-contact/membrane interface, so as to identify the conditions that eliminate the undesirable water layer in all solid-state polymeric ion sensors. In this work, we provide the first experimental evidence that the PMMA/PDMA copolymer system is susceptible to water ?pooling? at the interface in areas surrounding physical imperfections in the solid contact, with the exposure time for such an event in a PMMA/PDMA copolymer ISE taking nearly 20 times longer than that for a plasticized poly(vinyl chloride) (PVC) ISE, and the simultaneous use of a hydrophobic POT solid contact with a PMMA/PDMA membrane can eliminate totally this water layer problem.